Health and cleanliness : a text book for teachers - Green, George H. (George Henry), 1881- ; Buchan, G. F.; Muir, W. A. (London : Health and Cleanliness Council)
1938-03 1938 1930s 69 pages : illustrations APPENDIX 67 II. SUITABLE FOR REWARDING CLEANLINESS Painting Books and Colouring Cards for children. B. 33. Fairy Story — "Wedding-Day on Elfin Mount." Tickets, "Clean." Framed Pictures. Picture Postcards. Gilt Pocket Pencils. Electric Torches. Shoe and washing outfits. King Cleanliness and Queen Cleanliness. Coloured Crowns for boys and girls. III. OTHER MATERIAL SUITABLE FOR SCHOOLS B. 2. Hints for the Busy Housewife "—booklet B. 39. "The New Home "— booklet L. 32. "Clean Food "— leaflet Suitable for girls taking domestic science. B. 7. "Health and Beauty"— for girls B. 8. "Keep Fit" — for boys Books for "leavers." B. 9. Specimen Lesson for the use of teachers. B. 17. Syllabus of Lessons on "Health and Beauty." B. 18. Syllabus of Lessons based on Health and Cleanliness Council's posters. For Infants and Juniors. B. 19. Syllabus of Lessons for boys on "Keep Fit." B. 40. "A Little Book of Health" — for juniors. L. 45. Suggestions for the use of posters P. 58 and P. 71. L. 33A and L. 33B. "Am I ready for school?" — leaflets for junior girls and boys. L. 44. "Sparks for Lads" — leaflet for senior boys. L.-51. "Why Willie was willing to wash" — folder for juveniles. 177/5/8/3